An improved approximation algorithm for the s-t path movement problem - Wattana Jindaluang (2018)
© 2017, Chiang Mai University. All rights reserved. This paper considers a movement problem that minimizes the maximum movement of pebbles on a graph to form a path from source vertex s to destination vertex t. The best known algorithm for this problem is a 7-approximation algorithm developed by Berman, Demaine, and Zadimoghaddam in 2011. We refine the analysis of Berman et. al. to obtain an (3 + ϵ)-approximation algorithm for any constant ϵ > 0. This problem is a subroutine used by Berman et. al. for finding a solution to the connectivity movement problem. Using our improved algorithm as a subroutine, the approximation ratio for the connectivity movement problem improves from 136 to 104 + ϵ.